Logo

Łukasz 796 083 343 Grzegorz 731 857 989

Przykład 3

Przykład 3

Treść



Zasada ruchu środka masy 003_00

\(
\begin{align*}\\
&\hbox{W chwili początkowej układ był w spoczynku:}\\
&\dot x(0)=0\\
&x(0)=0\\
&\hbox{Wyznaczyć x(t) oraz nacisk N(t) na podłoże.}\\
\end{align*}\)

Rozwiązanie



Zasada ruchu środka masy 003_01

\(
\begin{align*}\\
&y=\omega t\\
&\omega=const.\\
&t=0, \ x=0, \ \dot x=0\\
&(M+3m)\ddot x_S=0\\
&(M+3m)\ddot y_S=N-(M+3m)g\\
\\
&(M+3m)\cdot x_S=M\cdot x+m(x+\frac{l}{2}cos\omega t)+m(x+\frac{3}{2}lcos\omega t)+m(x+2lcos\omega t)+C\\
&(M+m)\ddot x_S=(M+3m)\ddot x-4ml\omega^2 cos\omega t\\
&\ddot x=\frac{4m}{(M+3m)}l\omega^2 \cdot cos\omega t\\
&x=-\frac{4m}{(M+3m)}l\cdot cos\omega t+C_1\cdot t+C_2\\
&C_1=0, \ C_2=\frac{4m}{(M+3m)}\cdot l\\
&x=\frac{4m}{(M+3m)}l(1-cos\omega t)\\
\\
\\
&(M+m)y_s=m\frac{l}{2}sin\omega t+m\frac{l}{2}sin\omega t+C=mlsin\omega t+C\\
&(M+m)\ddot y_s=-ml\omega^2sin\omega t\\
&N=(M+3m)g+(M+3m)\ddot y_s=(M+3m)g-m\omega^2\cdot lsin\omega t\\
&N=(M+3m)g-m\omega^2lsin\omega t\\
\end{align*}\)